Graphene interface for detection of resorcinol an endocrine disruptor in solubilized ionic liquid system : electrochemical and COSMO-RS quantum studies - Rather, Jahangir Ahmad (2019)
We report synthesis, characterization and covalent fabrication of graphene nanosheets (GR) on Au electrode. The GR nanosheets were characterized by XRD, Raman spectroscopy, FESEM and TEM techniques. The GR nanosheets were functionalized by reduction of aryldiazonium salt (Cl−N2+–Ph–COOH) to produce GR–Ph–COOH. In another step, Au electrode was modified by cysteamine (Cyst) to form Au–S–CH2–CH2–NH2 surface. Finally, GR–Ph–COOH was covalently attached to Au–S–CH2–CH2–NH2 by carbodiimide chemistry. The GR–Cyst–Au interface was used for electrochemical determination of resorcinol (RS) in ionic liquid [C4mim] [Cl] system over a concentration range from 0.3 to 45.2 μM with a detection limit (LOD) of 0.02 μM. The faster electron transfers kinetics of RS in [C4 mim] [Cl] system was attributed to synergetic effects of GR nanosheets and [C4 mim] [Cl] medium. The GR–Cyst–Au interface was successfully applied for determination of RS in Garnier hair-color cream as a real sample analysis. Computational quantum approach i.e. COSMO-RS model was also used to study trend of interactions in a ternary mixture of water, RS and [C4 mim] [Cl] system for proposed RS sensor.